Cellular- and symbiont-mediated defenses in Bactrocera dorsalis (Hendel) and Ceratitis cosyra (Walker) against their native and introduced parasitoids - Weldon, Christopher W. (University of Pretoria, 2024)
Thesis (PhD (Zoology))--University of Pretoria, 2024.